Magnetospheric Science Objectives of the Juno Mission - Bagenal, F.; Adriani, A.; Allegrini, F.; Bolton, S. J.; Bonfond, B.; Bunce, E. J.; Connerney, J. E. P.; Cowley, S. W. H.; Ebert, R. W.; Gladstone, G. R.; Hansen, C. J.; Kurth, W. S.; et al. (Space science reviews, 2017)
In July 2016, NASA’s Juno mission becomes the first spacecraft to enter polar orbit of Jupiter and venture deep into unexplored polar territories of the magnetosphere. Focusing on these polar regions, we review current understanding of the structure and dynamics of the magnetosphere and summarize the outstanding issues. The Juno mission profile involves (a) a several-week approach from the dawn side of Jupiter’s magnetosphere, with an orbit-insertion maneuver on July 6, 2016; (b) a 107-day capture orbit, also on the dawn flank; and (c) a series of thirty 11-day science orbits with the spacecraft flying over Jupiter’s poles and ducking under the radiation belts. We show how Juno’s view of the magnetosphere evolves over the year of science orbits. The Juno spacecraft carries a range of instruments that take particles and fields measurements, remote sensing observations of auroral emissions at UV, visible, IR and radio wavelengths, and detect microwave emission from Jupiter’s radiation belts. We summarize how these Juno measurements address issues of auroral processes, microphysical plasma physics, ionosphere-magnetosphere and satellite-magnetosphere coupling, sources and sinks of plasma, the radiation belts, and the dynamics of the outer magnetosphere. To reach Jupiter, the Juno spacecraft passed close to the Earth on October 9, 2013, gaining the necessary energy to get to Jupiter. The Earth flyby provided an opportunity to test Juno ’s instrumentation as well as take scientific data in the terrestrial magnetosphere, in conjunction with ground-based and Earth-orbiting assets.